2022
DOI: 10.7554/elife.75873
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inflammation resolution requires CPEB4-directed offsetting of mRNA degradation

Abstract: Chronic inflammation is a major cause of disease. Inflammation resolution is in part directed by the differential stability of mRNAs encoding pro-inflammatory and anti-inflammatory factors. In particular, tristetraprolin (TTP)-directed mRNA deadenylation destabilizes AU-rich element (ARE)-containing mRNAs. However, this mechanism alone cannot explain the variety of mRNA expression kinetics that are required to uncouple degradation of pro-inflammatory mRNAs from the sustained expression of anti-inflammatory mRN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Apart from the regulation of CPEB activity through phosphorylation, the distance between the CPE and the poly(A) site was shown to be part of a combinatorial code that determines whether specific mRNAs are translationally activated (polyadenylated) or repressed (deadenylated) during meiotic progression of Xenopus oocytes [100]. Moreover, CPEB4 was recently found to stabilize CPE-and ARE-containing cytokine mRNAs in macrophages [101], indicating that cell-type-dependent differences may affect the function of CPEB4 within post-transcriptional regulatory complexes controlling the stability of selected mRNA subsets. In the future, it will be interesting to determine more precisely the molecular events that allow switching between the polyadenylation-promoting CPEB4activator complex and the CPEB4-repressor complex associated with CCR4-NOT-mediated mRNA deadenylation.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the regulation of CPEB activity through phosphorylation, the distance between the CPE and the poly(A) site was shown to be part of a combinatorial code that determines whether specific mRNAs are translationally activated (polyadenylated) or repressed (deadenylated) during meiotic progression of Xenopus oocytes [100]. Moreover, CPEB4 was recently found to stabilize CPE-and ARE-containing cytokine mRNAs in macrophages [101], indicating that cell-type-dependent differences may affect the function of CPEB4 within post-transcriptional regulatory complexes controlling the stability of selected mRNA subsets. In the future, it will be interesting to determine more precisely the molecular events that allow switching between the polyadenylation-promoting CPEB4activator complex and the CPEB4-repressor complex associated with CCR4-NOT-mediated mRNA deadenylation.…”
Section: Discussionmentioning
confidence: 99%
“…Spi1/PU.1) for myeloid cells and Rorc and Eomes for innate lymphoid cells. These TFs are likewise well-characterized master regulators of their respective lineages (Suñer et al ., 2022; Hoorweg et al ., 2012; Kiekens et al ., 2021). Importantly, these TFs were also highlighted in the original analysis, and overall the and TF by cell-type matrices are highly similar; an important difference, though, is that for the model these are simply model parameters and no additional post-hoc calculations were required.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophage identity was confirmed by flow cytometry (>95% were F4/80 + CD11b + , data not shown). BMDMs were then treated for 2 h with 40 mM EtOH 32 ± 10 ng/ml LPS 33,34 with or without 10 nM RvD1 35 . The concentrations used in this study are based on previously reported experimental conditions to elicit biological responses in macrophages.…”
Section: Methodsmentioning
confidence: 99%